Tracking and Assessing Oil Spill Toxicity to Aquatic Organisms: A Novel Approach. (10th March 2021) - Burton, G.A.; Cervi, E.C.; Rosen, G.; Colvin, M.; Chadwick, B.; Hayman, N.; Allan, S.E.; DiPinto, L.M.; Adams, R.; McPherson, M.; Scharberg, E.
Abstract: An in situ exposure and effects bioassay system was developed for assessing the toxicity of oil spills to aquatic organisms. The assessment tool combines components of 2 previously developed systems, the sediment ecotoxicity assessment ring (SEA Ring) and the drifting particle simulator. The integrated drifting exposure and effects assessment ring (DEEAR) is comprised of a Global Positioning System (GPS) float, a drifter drogue, the SEA Ring, and the Cyclops‐7 fluorescent sensor. Polyethylene passive sampling devices (PED) were mounted for an additional means to characterize water quality conditions and exposures. The DEEAR is optimized for evaluating oil exposure and toxicity in the shallow surface mixing layer of marine waters. A short‐term preliminary test was conducted in San Diego, California, USA, to verify the operation of the GPS tracking, the iridium communications, and the integrated SEA Ring exposure system. Further, a proof‐of‐concept demonstration was conducted offshore in the Santa Barbara Channel, where natural oil seeps produce surface slicks and sheens. Two DEEAR units were deployed for 24 h—one within the oil slick and one in an area outside observable slicks. An aerial drone provided tracking of the surface oil and optimal sites for deployment. The DEEAR proof‐of‐concept demonstrated integrated real‐time tracking and characterization of oil exposures by grab samples, PED, and fluorescent sensors. Oil exposures were directly linked to toxic responses in fish and mysids. This novel integrated system shows promise for use in a variety of aquatic sites to more accurately determine in situ oil exposure and toxicity. Environ Toxicol Chem 2021;40:1452–1462. © 2021 SETAC